2013
DOI: 10.1080/10410236.2012.714861
|View full text |Cite
|
Sign up to set email alerts
|

The Implications of Stigma and Anonymity for Self-Disclosure in Health Blogs

Abstract: The reported study examines the implications of anonymity and stigma in the form of illness-related embarrassment for self-disclosure in the context of health blogging. Drawing from theorizing about anonymous communication and stigma, anonymity is argued to be strategically used by individuals who are embarrassed by their illness and to moderate the relationship between embarrassment and self-disclosure. Data from 114 individuals who blog about their experiences coping with a health condition were examined to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(67 citation statements)
references
References 45 publications
2
64
0
1
Order By: Relevance
“…That this may be the case is reflected in a recent study which found a positive relationship between anonymity and self-disclosure among bloggers who were embarrassed by their ailments (Rains, 2014). Selfdisclosure is important to the extent that it promotes coping and helps draw in additional social support, a factor in promoting improvements in subjective wellbeing and understanding.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…That this may be the case is reflected in a recent study which found a positive relationship between anonymity and self-disclosure among bloggers who were embarrassed by their ailments (Rains, 2014). Selfdisclosure is important to the extent that it promotes coping and helps draw in additional social support, a factor in promoting improvements in subjective wellbeing and understanding.…”
Section: Discussionmentioning
confidence: 80%
“…By enabling people to express themselves in a relatively risk-free context, the anonymity blogging provides may be especially important for achieving catharsis and coping among those suffering from or caring for someone with a stigmatizing mental illness or condition (Boniel-Nissim & Barak, 2013;Ko & Kuo, 2009;Rains, 2014;Sundar et al, 2007). That this may be the case is reflected in a recent study which found a positive relationship between anonymity and self-disclosure among bloggers who were embarrassed by their ailments (Rains, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…We believe this may be relevant to take into account when considering to what extent an eating disorder may be exacerbated by various comments. According to Rains (2014), anonymity as a blogger may help mitigate the effects of a potential exacerbation and facilitate ongoing illnessrelated self-disclosure.…”
Section: Discussionmentioning
confidence: 99%
“…As noted above, we know that anonymity can cause disinhibition that has both positive (Rains, 2014;Turkle, 1995) and negative (Binns, 2013;E. Whittaker & Kowalski, 2015) effects.…”
Section: What Are People Doing?mentioning
confidence: 99%
“…As such, people could admit to common failings, such as poor academic performance, and reap the possible benefits of support (via upvotes) without being accountable or even visible to the people providing the support. In some ways this resembles prior online support forums or discussions (Rains, 2014;White & Dorman, 2001) but these were often characterized by persistent pseudonymous identity and revolved around longer-term support. On Yik Yak, identities and content are ephemeral.…”
Section: Implications For Theorymentioning
confidence: 99%